Implementasi Inovasi Pengaduan Online melalui Aplikasi Padang Kiniko di Dinas Kominfo Kota Padang - Karminos, Rizki; Magriasti, Lince (PUBLICNESS: Journal of Public Administration Studies, 2024)
This research analyzes the implementation of online complaints through the Padang Kiniko application, which still needs help in responding to and resolving public reports related to facilities in Padang City. This research was conducted using a qualitative approach at the KOMINFO Office of Padang City, with data obtained through in-depth interviews with the Padang Kiniko Application Admin Operator and the community using the application. The results showed that the implementation of the Padang Kiniko application was not optimal, which was caused by various obstacles, such as the limited number of admin operators in each OPD, the existence of repeated public reports, and the absence of notification features and user support services, such as call centers or customer service. To increase the effectiveness of the Padang Kiniko application implementation, it is recommended that the number of admin operators in each OPD be increased and notification features and user support services in the application be developed.